A history of the Vikings - Jones, Gwyn. (London Oxford University Press, 2002)
The subject of this book is the Viking realms, Denmark, Sweden, and Norway, their civilization and culture, and their many sided achievements at home and abroad.
Includes index.
Keywords: Includes index